DETEKSI DINI KEJADIAN HEPATITIS B PADA IBU HAMIL DI PROVINSI RIAU TAHUN 2019-2022 - Umaina, Ummi; Dewi, Oktavia; Anusirwan, Anusirwan (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
The problem of Hepatitis B in pregnant women increased from 2019-2022. Hepatitis B can occur in pregnant women due to transmission from other hepatitis sufferers in various ways, ranging from intercourse, the use of non-sterile needles together and various causes of hepatitis B in other pregnant women such as a history of transfusion, family history of hepatitis B and the use of toothbrushes. The purpose of the study was to determine the picture of early detection of hepatitis B cases in pregnant women in Riau Province in 2019-2022. This study used a descriptive quantitative approach conducted at the Riau Provincial Health Office in November-December of 2023. The study used secondary data obtained from the Riau Provincial Health Office report and analyzed descriptively. The results showed an increase in hepatitis B cases in pregnant women in 2019-2022, an increase in the number of pregnant women examined and still low efforts to examine 9-12 month HBsAf reactive infants during 2019-2022.Keywords: Pregnant Women, Hepatitis B, Needle Use